Bacterial community profiles on the surface of aluminum tray following contact with beef, chicken, and pork - Emamjomeh, Mohsen (2022)
Meat products are frequently linked to outbreaks of foodborne diseases. Bacteria have long been used in food products as a hygienic marker. As a result, increasing knowledge about the contribution of bacteria in food can impact determining proper food safety guidelines. Based on 16S rRNA amplicon metagenomic sequencing analyzed using the Illumina MiSeq system, this study aimed to determine the functional bacterial community structure, diversity, biomarkers, and taxa co-occurrence on food-associated surfaces used in industrial food preparation areas, i.e., aluminum tray, following contact with beef, pork, and chicken. Acinetobacter, Enterobacteriaceae family, Empedobacter, and Pseudomonas were the most abundant taxa on the beef-contact surface. Shewanella, Acinetobacter, Pseudomonas, and Aeromonas were prevalent in chicken-contact trays, whereas Acinetobacter, Myroides, Pseudomonas, and Serratia were prevalent in porkcontact trays. Trays that had been in contact with chicken had the highest species evenness and richness, followed by pork and beef. The diversity between chicken, beef, and pork-contacted trays was significantly different. Kocuria, Soonwooa, Myroides, Bacillus, Escherichia-Shigella, Rummeliibacillus, in beef, Alteromonadales, Klebsiella, Flavobacterium, and Aquitalea in chicken, while Comamonadaceae, Xanthomonadaceae, Flavobacterium, Staphylococcus, Wohlfahrtiimonas, Weissella, and Vitreoscilla genera in pork, were detected as hub nodes. Most of the hub nodes could cause human or animal diseases, and some of them were antibiotic resistant. In addition, bacterial markers were identified in each meat type, and some of them were pathogens such as Shewanella in chicken, Klebsiella in pork, and Staphylococcus in beef. The prediction of functional metagenomic content demonstrated that the enzymes, KEGG orthologs, and biochemical pathways in the various meats were similar. Some proteins, however, were discriminant between meat groups. Methyl-accepting chemotaxis protein was significantly more abundant in chicken samples than in beef samples, which is beneficial in bacteria colonization. The enzymes beta-glucosidase and glutamine synthetase, which are commonly associated with sepsis, were significantly higher in chicken than in pork. In conclusion, bacterial pathogens were found on the aluminum trays despite applying usual storage procedures, indicating that proper hygienic practice and regular cleaning of food preparation areas and utensils are required to avoid crosscontamination. This study has provided detailed information about the bacterial taxa found on the surface of trays after contact with meats, which will be useful in developing appropriate guidance for safer food handling in the future. Further research into the differences in the bacterial community in other meats can be conducted.